Hibernation strategy – related profound differences in the whole-body fat composition of bats ... - Bachorec, Erik; Pikula, Jiří; Seidlová, Veronika; Zukalová, Kateřina; Zukal, Jan (Zenodo, 2023)
(Uploaded by Plazi for the Bat Literature Project) Bats can use a wide range of roosts as hibernacula, resulting in diverse hibernation strategies. The ecological needs of a species during hibernation translate into particular torpor-arousal patterns and physiological demands. For mammalian hibernators, the oxidation of fatty acids from triacylglycerols stored in white and brown adipocytes provides the main energy to fuel hibernation. The relative content of saturated, monounsaturated, and polyunsaturated fatty acids in body fat brings multifarious costs and benefits, and their importance during hibernation is likely changing. While considering the level of fatty acid saturation and their properties, we hypothesised that whole-body fat composition varies between bat species (Nyctalus noctula, Myotis myotis) that employ different hibernation strategies. Therefore, the focus of this study was to determine the relative fatty acid composition of the whole-body fat of these species. We found evidence that the ...